Global Analysis of WRKY Genes and Their Response to Dehydration and Salt Stress in Soybean - Song, Hui; Wang, Pengfei; Hou, Lei; Zhao, Shuzhen; Zhao, Chuanzhi; Xia, Han; Li, Pengcheng; Zhang, Ye; Bian, Xiaotong; Wang, Xingjun (Frontiers in Plant Science, 2016)
WRKY proteins are plant specific transcription factors involved in various developmental and physiological processes, especially in biotic and abiotic stress resistance. Although previous studies suggested that WRKY proteins in soybean (Glycine max var. Williams 82) involved in both abiotic and biotic stress responses, the global information of WRKY proteins in the latest version of soybean genome (Wm82.a2v1) and their response to dehydration and salt stress have not been reported. In this study, we identified 176 GmWRKY proteins from soybean Wm82.a2v1 genome. These proteins could be classified into three groups, namely group I (32 proteins), group II (120 proteins), and group III (24 proteins). Our results showed that most GmWRKY genes were located on Chromosome 6, while chromosome 11, 12 and 20 contained the least number of this gene family. More GmWRKY genes were distributed on the ends of chromosomes to compare with other regions. The cis-acting elements analysis suggested that GmWRKY genes were transcriptionally regulated upon dehydration and salt stress. RNA-seq data analysis indicated that three GmWRKY genes responded negatively to dehydration, and 12 genes positively responded to salt stress at 1, 6 and 12 h, respectively. We confirmed by qRT-PCR that the expression of GmWRKY47 and GmWRKY 58 genes was decreased upon dehydration, and the expression of GmWRKY92, 144 and 165 genes was increased under salt treatment.